THE INFLUENCE OF PHOTOSENSITIVE PEPTIDOMIMETICS ON WEIGHT INDICES OF IMMUNE ORGANS OF EXPERIMENTAL ANIMALS WITH TRANSPLANTABLE LEWIS LUNG CARCINOMA - Volodkina D.; Stupak I.; Senchylo N.; Molozhava O.; Garmanchuk L. (Biotechnologia Acta, 2022)
The use of photodynamic therapy of drugs capable of selective accumulation in the tumor or in affected cells, in particular photosensitive peptidomimetics, increases its effectiveness in various treatment schemes.